2011
DOI: 10.1093/intimm/dxr104
|View full text |Cite
|
Sign up to set email alerts
|

HCV core and NS3 proteins manipulate human blood-derived dendritic cell development and promote Th 17 differentiation

Abstract: Hepatitis C virus (HCV) chronic infection is characterized by low-level or undetectable cellular immune response against HCV antigens. HCV proteins affect various intracellular events and modulate immune responses, although the mechanisms that mediate these effects are not fully understood. In this study, we examined the effect of HCV proteins on the differentiation of human peripheral blood monocytes to dendritic cells (DCs). The HCV core (HCVc) and non-structural 3 (NS3) proteins inhibited the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…It has been reported that HCVc induces TLR2-mediated activation of monocytes171923, and manipulates monocyte differentiation into dendritic cells21. Thus, we next investigated whether the impaired M1 and M2 macrophage polarization in patients with HCV infection was mediated by HCVc.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that HCVc induces TLR2-mediated activation of monocytes171923, and manipulates monocyte differentiation into dendritic cells21. Thus, we next investigated whether the impaired M1 and M2 macrophage polarization in patients with HCV infection was mediated by HCVc.…”
Section: Resultsmentioning
confidence: 95%
“…Increased level of TLR2 and TLR4 expression were observed in peripheral monocytes of patients with HCV infection, and increased expression of TLR2 is particularly associated with an increase in circulating TNF-α level and hepatic inflammatory activity20. Our previous study showed that HCVc inhibits monocyte differentiation into dendritic cells (DCs)21.…”
mentioning
confidence: 99%
“…6,7 Briefly, protein-free, phenol-water extracted ultrapure Escherichia coli LPS was used to create a linear standard curve from 1 to 100 pg/ml. HCVc was serially diluted to determine a concentration of agonist within the standard curve of the assay.…”
Section: Limulus Amebocyte Lysate Assay For Detection Of Lps Contaminmentioning
confidence: 99%
“…6,7 T lymphocyte subsets proliferation assays CD8 1 , CD4 1 , CD4 1 CD25 1 Treg and CD4 1 CD25 2 T-cell subsets were stained with 5 mM CFSE (Molecular Probes, Grand Island, NY. USA) according to the manufacturer's recommended protocol.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
See 1 more Smart Citation